PENGARUH TEKNIK RELAKSASI NAPAS DALAM TERHADAP SKALA NYERI PADA PASIEN POST OPERASI DI RUANG RAWAT INAP RUMAH SAKIT BAYUKARTA - Sari, Sari Sarce Andriana; Nurjamilah, Nurjamilah; Ngadiran, Antonius (Jurnal Ilmu Kesehatan Immanuel, 2024)
Pain is an unpleasant subjective sensory and emotional experience associated with actual or potential tissue damage. Pain management can be done in two ways, namely pharmacological and non-pharmacological. One of the non-pharmacological pain management is deep breathing relaxation techniques. This study aims to determine the effect of deep breathing relaxation techniques on pain scale in postoperative patients in the inpatient room at Bayukarta Hospital, Karawang. The design of this study used accidental sampling with a quasi-experimental design with a pre-post test design approach with a control group. The number of samples in this study amounted to 36 people (18 people in the control group and 18 people in the intervention group). The instrument in this study used an observation sheet and a pain measuring instrument using the Numeric Rating Scale (NRS). Statistical test paired T-test in the intervention group and control group postoperative patient pain scale after being given deep breathing relaxation techniques with a postoperative patient pain scale before deep breathing relaxation techniques with a significance level of 95%, showed that the p-value was 0.000 ( p<0.05), meaning that Ho is rejected and Ha is accepted. There is an Influence of Deep Breathing Relaxation Techniques on Pain Scale in Surgery Patients in the Inpatient Room of Bayukarta Hospital, Karawang.